Manganese-copper alloy composite material and preparation method thereof
By adding composite particles to the manganese copper alloy and adopting an optimized preparation process, the problem of the failure of the manganese copper alloy material performance is solved, and the hardness, wear resistance and corrosion resistance of the material have been greatly improved.
Patent Information
- Application Number
- CN202510313969.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-06-27
AI Technical Summary
The existing manganese copper alloy preparation methods are difficult to achieve comprehensive improvement of material performance, and there are problems of uneven particle distribution and intimate interface bonding, resulting in the failure of the material performance to achieve the best.
High-purity copper powder, manganese powder, silicon powder are used to mix evenly with composite particles, mix through a ball mill, followed by hot pressing, sintering, aging treatment, hot rolling or hot extrusion treatment, and finally polishing or coating surface treatment.
By adding composite particles and optimizing the preparation process, the hardness, wear resistance and corrosion resistance of manganese-copper alloy are significantly improved, the overall improvement of material performance is achieved, internal stress is reduced, and crack resistance is improved.
Smart Images

Figure CN120210582A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite alloy preparation, and particularly relates to a manganese copper alloy composite material and a preparation method thereof. Background Art
[0002] With the continuous improvement of the requirements for material properties in modern industry, especially in terms of high strength, high wear resistance, corrosion resistance, etc., traditional alloy materials can no longer meet the needs of some high-end application fields. There is often a need for some composite alloys, especially manganese copper alloys. As a material with good strength and corrosion resistance, it is widely used in industries such as aerospace, ocean engineering, and electronic devices.
[0003] Manganese copper alloys often improve the hardness, wear resistance, and corrosion resistance of materials by adding alloying elements. However, in the prior art, the distribution of reinforcing particles is still uneven, and the interfacial bonding between particles and the matrix is not tight enough, resulting in the performance of alloy materials not reaching the best. Existing preparation methods of manganese copper alloys mostly focus on single material enhancement, and it is often difficult to achieve a comprehensive improvement in material properties. In addition, insufficient temperature control and process adjustment during the manufacturing process often lead to defects such as pores and cracks in the alloy during the forming process, affecting the use performance of the material. Moreover, existing alloy materials often have certain problems in the distribution, stability of the reinforcing phase, and its bonding force with the matrix, making it difficult to achieve uniform dispersion of particles and good interfacial bonding, restricting the further improvement of their performance. How to enhance the various properties of manganese copper alloys by reasonably designing alloy compositions and optimizing preparation processes is an urgent problem to be solved. Summary of the Invention
[0004] The purpose of the present invention is to solve the defects existing in the prior art, and to provide a manganese copper alloy composite material and a preparation method thereof.
[0005] To achieve the above purpose, the present invention adopts the following technical solutions:
[0006] A preparation method of a manganese copper alloy composite material includes the following steps:
[0007] Step 1: Use copper powder, manganese powder, and silicon powder with a purity of more than 99.9% as the main elements of the matrix alloy, and use composite particles as the reinforcing phase, with a mass percentage of 5% - 10% and a particle size of 100 nm to 1 μm;
[0008] Step 2: Uniformly mix the copper powder, manganese powder, silicon powder, and composite particles according to the mass percentage, and use a ball mill for mixing. The ball milling time is 2 - 4 hours, and the ball milling speed is 200 - 300 rpm. An argon or inert gas environment is used during the mixing process to prevent powder oxidation;
[0009] Step 3: Load the uniformly mixed powder into a mold and perform hot pressing. Control the hot pressing temperature at 800 - 1000 °C, the pressure at 30 - 50 MPa, the heating rate at 10 - 20 °C / min, and the holding time at 30 - 60 minutes to enable the powder to undergo plastic flow and form a predetermined shape;
[0010] Step 4: After hot pressing, sinter the material. The sintering temperature is 1050 - 1200 °C, the holding time is 2 - 4 hours, and sintering is carried out using a vacuum or argon protective atmosphere;
[0011] Step 5: Perform aging treatment on the sintered alloy material. The aging temperature is 300 - 400 °C, the holding time is 3 - 8 hours, and cooling treatment is carried out after aging;
[0012] Step 6: Perform hot rolling or hot extrusion treatment. The heat treatment temperature is 800 - 1000 °C, and the hot extrusion or rolling pressure is 10 - 30 MPa;
[0013] Step 7: Perform polishing or coating surface treatment on the prepared alloy composite material to complete the preparation.
[0014] Furthermore, the manganese - copper alloy composite material comprises the following components by mass percentage:
[0015] Cu: 80% - 85%, Mn: 10% - 15%, Si: 2% - 4%, dissolved gas: ≤1% (impurities or dissolved gas), and composite particles: 5% - 10%.
[0016] Furthermore, the composite particles are composed of the following components by mass percentage:
[0017] AlO: 30%, SiN: 30%, and HA: 40%.
[0018] Furthermore, in Step 1, the surface of the composite particles is treated with a silane coupling agent.
[0019] Furthermore, in Step 3, argon is used for stirring to ensure the uniform distribution of the composite particles in the molten metal. During stirring, ultrasonic assistance is adopted to stir the molten metal.
[0020] Furthermore, in Step 2, particle layering is carried out to control the particle types and ratios in different regions, forming a composition gradient of the alloy material. Among them, copper powder, manganese powder, and silicon powder account for not less than 80%, and the balance is a proportional mixture of silicon nitride and alumina as reinforcing particles, which is used as the central region of the alloy;
[0021] The remaining material is distributed in the outer layer region to form a strengthening layer.
[0022] Furthermore, in Step 5, spray cooling is used to cool the outer layer of the material, and its internal center is cooled by natural cooling.
[0023] Furthermore, in Step 5, a gradient heating method is adopted, and the specific steps are as follows:
[0024] Set three different heating zones: upper, middle, and lower, and gradually heat the temperature of each zone. Among them,
[0025] Upper zone: The part close to the upper mold is heated to 90 - 1000 °C;
[0026] Middle zone: The temperature of the part close to the middle mold is between 800 - 900 °C;
[0027] Lower zone: The part close to the bottom mold is heated to 700 - 800 °C, where:
[0028] Control the temperature difference between the surface and the center to be 50 - 100 °C;
[0029] Heating rate: 5 - 10 °C / min.
[0030] Furthermore, the heating source in the upper zone adopts a gradually heating method, where:
[0031] In the middle and lower zones, the temperature changes every 15 minutes. Each time the temperature change refers to the temperature in the upper zone, which is lower than the temperature in the upper zone, and the maximum difference does not exceed 50 °C;
[0032] Carry out segmented heating, and the heating rate for each segment is 10 °C / min. The segments include:
[0033] Preheating stage:
[0034] Surface temperature: 800 °C;
[0035] Center temperature: 700 °C;
[0036] Heating time: 60 minutes;
[0037] Main heating stage:
[0038] Surface temperature: 1000 °C;
[0039] Center temperature: 900 °C;
[0040] Heating time: 30 minutes;
[0041] Heating end stage:
[0042] Surface temperature: 1000 °C;
[0043] Center temperature: 900 °C;
[0044] Heating time: 20 minutes;
[0045] Control the temperature difference: 50 - 100 °C, which is used to ensure that the surface and center temperature difference does not exceed this range.
[0046] Furthermore, in Step 6, place the alloy material after hot extrusion treatment in a sealed high-pressure environment, control the temperature at 700 - 900 °C, maintain an isostatic pressure of 400 - 600 MPa, and continue for more than 30 minutes.
[0047] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0048] By adding composite particles (such as alumina, silicon nitride, hydroxyapatite, etc.) as reinforcement phases to the manganese copper alloy, the hardness and wear resistance of the alloy can be significantly improved. Hard particles such as alumina and silicon nitride are evenly distributed in the alloy to form a strengthening phase, greatly enhancing the wear resistance of the material;
[0049] By adopting the particle layering technology in the alloy preparation process, controlling the particle type and ratio in different regions, the composition and structure gradient inside the material are effectively realized. Especially by increasing the reinforcement particles such as silicon nitride and alumina in the outer layer region to form a strengthening layer, while the matrix region maintains a relatively low particle content, ensuring the comprehensive performance and mechanical stability of the alloy. In addition, by adopting the preparation process of gradient heating and temperature gradient control, the temperature distribution of the alloy can be effectively controlled, reducing the internal stress of the material and improving its crack resistance. In the processes of hot pressing, sintering, aging, etc., through the optimized temperature control program, the bonding force between the reinforcement phase particles and the matrix metal is further enhanced, ensuring the overall performance and long service life of the material, and successfully realizing the comprehensive improvement of the performance of the manganese copper alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] The drawings are used to provide a further understanding of the present invention, and constitute a part of the specification. They are used together with the embodiments of the present invention to explain the present invention, and do not constitute a limitation to the present invention.
[0051] Figure 1 It is a schematic flow chart of the preparation method of the manganese copper alloy composite material in the embodiment of the present invention; DETAILED DESCRIPTION OF THE EMBODIMENTS
[0052] The following will clearly and completely describe the technical solutions in the embodiments of the present invention with reference to the drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments.
[0053] As Figure 1 shown, a preparation method of a manganese copper alloy composite material includes the following steps:
[0054] Step 1: Use copper powder, manganese powder, and silicon powder with a purity of over 99.9% as the main elements of the matrix alloy, and use composite particles as the reinforcing phase, with a mass percentage of 5%-10% and a particle size of 100 nm to 1 μm;
[0055] Among them, the surface of the composite particles is treated with a silane coupling agent.
[0056] Step 2: Uniformly mix the copper powder, manganese powder, silicon powder, and composite particles according to the mass percentage, and use a ball mill for mixing. The ball milling time is 2-4 hours, the ball milling speed is 200-300 rpm, and an argon or inert gas environment is used during the mixing process to prevent powder oxidation;
[0057] Step 3: Load the uniformly mixed powder into a mold and perform hot pressing. The hot pressing temperature is controlled at 800-1000 °C, the pressure is 30-50 MPa, the heating rate is 10-20 °C / min, and the holding time is 30-60 minutes to make the powder undergo plastic flow and form a predetermined shape;
[0058] Among them, argon stirring is used to ensure the uniform distribution of the composite particles in the molten metal. Among them, ultrasonic assistance is used for stirring the molten metal during stirring.
[0059] Step 4: After hot pressing, sinter the material. The sintering temperature is 1050-1200 °C, the holding time is 2-4 hours, and a vacuum or argon protective atmosphere is used for sintering;
[0060] Step 5: Perform aging treatment on the sintered alloy material. The aging temperature is 300-400 °C, the holding time is 3-8 hours, and cooling treatment is performed after aging;
[0061] Step 6: Perform hot rolling or hot extrusion treatment. The heat treatment temperature is 800-1000 °C, and the hot extrusion or rolling pressure is 10-30 MPa;
[0062] Step 7: Perform polishing or coating surface treatment on the prepared alloy composite material to complete the preparation.
[0063] Example 1
[0064] A method for preparing a manganese copper alloy composite material, the manganese copper alloy composite material comprising the following components by mass percentage:
[0065] Cu: 80%-85%, Mn: 10%-15%, Si: 2%-4%, dissolved gas: ≤1% (impurities or dissolved gas), and composite particles: 5%-10%;
[0066] In a specific embodiment of the present application, the composite particles are composed of the following components by mass percentage:
[0067] AlO: 30%, SiN: 30%, HA: 40% (by mass).
[0068] It should be noted that Cu80%-85%: Copper, as the matrix metal, has excellent electrical conductivity, ductility, and corrosion resistance. Maintaining a relatively high copper content helps ensure the good electrical conductivity of the alloy and provides appropriate plasticity and ductility.
[0069] Mn10%-15%: Manganese element plays a strengthening role in copper alloys, improving the wear resistance and strength of the material. At the same time, manganese can improve the oxidation resistance and corrosion resistance of the alloy, especially showing more prominent performance in high-temperature environments. Selecting a manganese content of 10%-15% can ensure strength without affecting the plasticity of the material.
[0070] Si: 2%-4%: The addition of silicon improves the heat resistance and oxidation resistance of the alloy, and at the same time promotes the fluidity of the alloy, making the alloy easier to form. A silicon content of 2%-4% is to balance the fluidity and strength of the alloy, ensuring that the alloy has good processing performance and high-temperature performance.
[0071] Composite particles: 5%-10%: The addition of reinforcing particles is to improve the hardness, wear resistance, and corrosion resistance of the alloy. The content of composite particles is set between 5% and 10%, which can enhance the alloy performance without affecting its plasticity and toughness. Excessive particle content may lead to an increase in material brittleness. Selecting this range can balance the enhanced performance and the plasticity of the material.
[0072] Among them, in the composite particle formulation, AlO: As a common ceramic material, alumina has excellent wear resistance, oxidation resistance, and relatively high hardness. Selecting 30% alumina as the reinforcing phase can effectively improve the wear resistance of the material;
[0073] SiN: Silicon nitride has high strength, good high-temperature resistance, and thermal shock resistance. Adding silicon nitride particles can further enhance the high-temperature performance and mechanical properties of the alloy.
[0074] HA: Hydroxyapatite, as a biomaterial, can increase the biocompatibility of the material. It can effectively improve the fatigue resistance and corrosion resistance of the material. Selecting a proportion of 40% helps optimize the biological properties of the alloy while maintaining good mechanical properties.
[0075] Example 2
[0076] Based on Example 1, in Step 2, particle layering is carried out to control the particle types and ratios in different regions, forming a composition gradient of the alloy material. Among them, copper powder, manganese powder, and silicon powder account for no less than 80%, and the balance is an equal-proportion mixture of silicon nitride and alumina reinforcing particles, which is used as the central region of the alloy;
[0077] The surplus material is distributed in the outer layer area to form a strengthening layer.
[0078] In step five, spray cooling is used to cool the outer layer of the material, and its internal center is cooled by natural cooling.
[0079] In a specific embodiment of the present application, in step five, a gradient heating method is adopted, and the specific steps are as follows:
[0080] Set three different heating areas: upper, middle, and lower, and gradually heat the temperature of each area. Among them,
[0081] Upper area: The part close to the upper mold is heated to 90 - 1000 °C;
[0082] Middle area: The temperature of the part close to the middle mold is between 800 - 900 °C;
[0083] Lower area: The part close to the bottom mold is heated to 700 - 800 °C, where:
[0084] Control the temperature difference between the surface and the center to be 50 - 100 °C.
[0085] Heating rate: 5 - 10 °C / min
[0086] Preferably, the heating source in the upper area adopts a gradually heating method, where:
[0087] In the middle and lower areas, the temperature changes every 15 minutes. Each time the temperature change refers to the temperature in the upper area, which is lower than the temperature in the upper area, and the maximum difference does not exceed 50 °C;
[0088] Carry out segmented heating, and the heating rate of each segment is 10 °C / min. The segments include:
[0089] Preheating stage:
[0090] Surface temperature: 800 °C
[0091] Center temperature: 700 °C;
[0092] Heating time: 60 minutes;
[0093] Main heating stage:
[0094] Surface temperature: 1000 °C;
[0095] Center temperature: 900 °C;
[0096] Heating time: 30 minutes;
[0097] Heating end stage:
[0098] Surface temperature: 1000 °C;
[0099] Central temperature: 900 °C;
[0100] Heating time: 20 minutes;
[0101] Controlled temperature difference: 50 - 100 °C, used to ensure that the surface and central temperature difference does not exceed this range.
[0102] In another specific embodiment of the present application, in step six, the alloy material after hot extrusion treatment is placed in a sealed high-pressure environment, the temperature is controlled at 700 - 900 °C, and an isostatic pressure of 400 - 600 MPa is maintained for more than 30 minutes.
[0103] To better understand the technical solution of the present application, the following is further illustrated with examples.
[0104] Experimental purpose:
[0105] Verify the technical effects and advantages of the composite material through the differences in hardness, wear resistance, and corrosion resistance between the manganese copper alloy composite material prepared by the steps of the above embodiments and the sample material (without reinforcing particles).
[0106] Example: Obtain the alloy composite material according to the steps of the embodiments of the present application
[0107] Control group: Any manganese copper alloy. (The component ratio of the manganese copper alloy selected for this experiment is: Cu: 85%, Mn: 10%, and Si: 2%.
[0108] Experimental steps:
[0109] Hardness test: Measure the hardness of the alloy sample using a Vickers hardness tester.
[0110] Wear resistance test: Use a wear tester and adopt the dry friction wear test method to measure the wear rate.
[0111] Corrosion resistance test: Use a salt spray test to test the corrosion resistance of the alloy, and the test cycle is 48 hours.
[0112] Specific parameter settings are as follows:
[0113] Hardness test: Test load: 100 g; Test time: 15 seconds; Test spacing: 5 mm
[0114] Wear resistance test: Load: 10 N; Rotation speed: 200 rpm; Wear time: 2 hours
[0115] Salt spray test: Temperature: 35 °C; Concentration of sodium chloride solution: 5%; Spray time: 48 hours. The specific results are shown in Table 1.
[0116] Table 1
[0117]
[0118] As can be seen from Table 1, the hardness of the solution of the present invention is 180 HV, while the hardness of the comparative example is 140 HV, indicating that by adding composite particles (aluminum oxide, silicon nitride, hydroxyapatite), the hardness of the alloy is significantly improved. This is because hard particles such as aluminum oxide and silicon nitride effectively improve the compressive strength and hardness of the alloy.
[0119] In addition, in the wear resistance test, the wear rate of the solution of the present invention is 0.015 mm 3 / (N·m). The addition of composite particles (especially aluminum oxide and silicon nitride) greatly improves the wear resistance of the material and reduces the wear rate. The composite particles are evenly distributed in the alloy, forming a stronger material surface and further improving the wear resistance.
[0120] The solution of the present invention shows better corrosion resistance in the salt spray test. There is no obvious corrosion after 12 hours. The introduction of composite particles, especially silicon nitride and aluminum oxide, enhances the oxidation resistance of the alloy, thus effectively improving the corrosion resistance of the material.
[0121] As can be seen from the above, through the experimental results, it can be seen that the composite manganese copper alloy has significantly higher hardness, wear resistance and corrosion resistance compared with the traditional manganese copper alloy. The improvement of these properties proves the effectiveness of the composite reinforcing particles (aluminum oxide, silicon nitride and hydroxyapatite) proposed in the solution of the present invention, indicating that the alloy material of the present invention has a wider application prospect, especially suitable for fields with high requirements for high strength, high wear resistance and corrosion resistance.
[0122] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art within the technical scope disclosed by the present invention, according to the technical solution and inventive concept of the present invention, makes equivalent substitutions or changes, and should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a manganese-copper alloy composite material, characterized in that: The following steps are involved: Step 1: using copper powder, manganese powder and silicon powder with a purity of more than 99.9% as the main elements of the matrix alloy, and using composite particles as the reinforcement phase, with a mass percentage of 5%-10% and a particle size of 100nm to 1μm; Step 2: Evenly mix the copper powder, manganese powder, silicon powder and composite particles according to the mass percentage, use a ball mill to mix, the ball milling time is 2-4 hours, the ball milling speed is 200-300rpm, and argon or inert gas environment is used during the mixing process to prevent powder oxidation; Step 3: Put the evenly mixed powder into the mold and perform hot pressing molding. The hot pressing temperature is controlled at 800-1000°C, the pressure is 30-50MPa, the heating rate is 10-20°C / min, and the holding time is 30-60 minutes, so that the powder undergoes plastic flow and forms a predetermined shape; Step 4: After hot pressing, the material is sintered at a temperature of 1050-1200°C for 2-4 hours in a vacuum or argon protective atmosphere; Step 5: subjecting the sintered alloy material to aging treatment at a temperature of 300-400°C for 3-8 hours, followed by cooling treatment after the aging treatment is completed; Step 6: hot rolling or hot extrusion treatment, the heat treatment temperature is 800-1000°C, and the hot extrusion or rolling pressure is 10-30MPa; Step seven: polishing or coating the prepared alloy composite material to complete the preparation.
2. The method for preparing the manganese-copper alloy composite material according to claim 1, characterized in that: The manganese-copper alloy composite material comprises the following components in percentage by mass: Cu: 80%-85%, Mn: 10%-15%, Si: 2%-4%, dissolved gas: ≤1% and composite particles: 5%-10%.
3. The method for preparing the manganese-copper alloy composite material according to claim 2, characterized in that: The composite particles are composed of the following components in percentage by weight: AlO: 30%, SiN: 30% and HA: 40%.
4. The method for preparing the manganese-copper alloy composite material according to claim 3, characterized in that: In step one, the composite particles are treated with a silane coupling agent on the particle surface.
5. The method for preparing the manganese-copper alloy composite material according to claim 4, characterized in that: In step three, argon gas is used for stirring to ensure uniform distribution of the composite particles in the molten metal, wherein ultrasonic waves are used to assist in stirring the molten metal.
6. The method for preparing the manganese-copper alloy composite material according to claim 5, characterized in that: In step 2, the particles are layered to control the particle types and proportions in different regions to form a composition gradient of the alloy material, wherein copper powder, manganese powder, and silicon powder account for no less than 80%, and the remainder is a mixture of silicon nitride and aluminum oxide in equal proportions to strengthen the particles, which are used as the central region of the alloy; The remaining material is distributed in the outer area to form a strengthening layer.
7. The method for preparing the manganese-copper alloy composite material according to claim 6, characterized in that: In step 5, a gradient heating method is used, and the specific steps are as follows: Set up three different heating areas: upper, middle and lower, and gradually increase the temperature of each area. Upper zone: The part close to the upper mold is heated to 90-1000℃; Middle zone: The temperature near the middle mold is 800-900℃; Lower zone: The part close to the bottom mold is heated to 700-800℃, where: Control the temperature difference between the surface and the center to be 50-100℃; Heating rate: 5-10℃ / min.
8. The method for preparing the manganese-copper alloy composite material according to claim 7, characterized in that: The upper zone heating source adopts a gradual heating method, in which: The temperature of the middle and lower zones changes every 15 minutes. Each temperature change is based on the temperature of the upper zone, which is lower than the temperature of the upper zone, and the maximum difference does not exceed 50°C. The heating is carried out in sections, and the heating rate of each section is 10°C / min. The sections include: Preheating stage: surface temperature: 800°C; center temperature: 700°C; heating time: 60 minutes; Main heating stage: surface temperature: 1000℃; center temperature: 900℃; heating time: 30 minutes; Heating end stage: surface temperature: 1000℃; center temperature: 900℃; heating time: 20 minutes; Control temperature difference: 50-100℃, to ensure that the temperature difference between the surface and the center does not exceed this range.
9. The method for preparing the manganese-copper alloy composite material according to claim 8, characterized in that: In step six, the alloy material after hot extrusion treatment is placed in a closed high-pressure environment, the temperature is controlled at 700-900° C., and the isostatic pressure is maintained at 400-600 MPa for more than 30 minutes.
10. A manganese-copper alloy composite material, characterized in that: Prepared according to any one of claims 1 to 9.
Citation Information
Cited By
Gradient component preparation method of manganese-copper alloy with improved toughness
CN120485573A
